The Analytics of Performance Measurement Using a Security Market Line - DYBVIG, PHILIP H.; ROSS, STEPHEN A. (Journal of Finance, 1985)
ABSTRACT Security market line (SML) analysis, while an important tool, has never been fully justified from a theoretical standpoint. Assuming symmetric information and an inefficient index, we show that SML analysis can be grossly misleading, since, in general, efficient and inefficient portfolios can plot above and below the SML. On a more positive note, if SML analysis uses the return on a marketed riskless asset for the zero‐beta rate, efficient portfolios must plot above the SML. Nonetheless, arbitrarily inefficient portfolios also plot above the SML.